Fatigue Analysis of a Wave Energy Converter Taking into Account Different Control Strategies - Zurkinden, Andrew Stephen; Lambertsen, Søren Heide; Damkilde, Lars; Gao, Zhen; Moan, Torgeir (Volume 8: Ocean Renewable Energy, 2013)
Point absorber wave energy converters (WEC) are subjected to random wave loads. In addition, the power production of a WEC and the motions are considerably influenced by the applied control mechanism. For small waves, with a wave period close to the natural period of the oscillating system, the power output may be controlled passively by means of a constant damping coefficient. The energy is extracted proportionally to the square of the body′s velocity. If the wave period is away from the natural period, reactive power may be applied in order to enlarge the resonance bandwidth. Recent studies on a point absorber have shown that the stresses at a particular section of the structure depend on the control parameters. The power is increased by choosing a more advanced control mechanism. The consequences are that the stress amplitudes are higher than for the more conservative control case. In this study, the focus is given on the fatigue damage calculation of a structural detail by taking into account the control parameters of the power take-off system. The predicted fatigue damage is calculated based on the spectral approach. Finally the question will be answered which control strategy is more favorable regarding the trade off between the fatigue damage and power production of the wave energy device. Point absorber wave energy converters (WEC) are subjected to random wave loads. In addition, the power production of a WEC and the motions are considerably influenced by the applied control mechanism. For small waves, with a wave period close to the natural period of the oscillating system, the power output may be controlled passively by means of a constant damping coefficient. The energy is extracted proportionally to the square of the body′s velocity. If the wave period is away from the natural period, reactive power may be applied in order to enlarge the resonance bandwidth. Recent studies on a point absorber have shown that the stresses at a particular section of the structure depend on the control parameters. The ...